2022
DOI: 10.1128/aac.02392-21
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Binding Pocket Arg717 Substitutions in Escherichia coli AcrB Cause Clinically Relevant Divergencies in Resistance Profiles

Abstract: Recent mutations in RND efflux pumps in clinical strains have further increased multidrug resistance. We show that R717L and R717Q substitutions (found in azithromycin-resistant Salmonella enterica spp.) in the Escherichia coli efflux pump AcrB dramatically increase macrolide, as well as fluoroquinolone, resistance.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…To our best knowledge, the genetic context of the three Salmonella serovars containing erm (42) reported in this study (on IncQ plasmids) is novel. Mutation in the RND-type transporter gene ( acrB _R717L/Q), which has been reported mostly in S. Typhi and S. Paratyphi A, has been confirmed recently to confer azithromycin resistance in E. coli by cloning ( 34 , 35 ). The first Arg717 substitution was predicted to have emerged around 2010 with travel-related R717Q mutant found in the United Kingdom ( 36 ).…”
Section: Discussionmentioning
confidence: 92%
“…To our best knowledge, the genetic context of the three Salmonella serovars containing erm (42) reported in this study (on IncQ plasmids) is novel. Mutation in the RND-type transporter gene ( acrB _R717L/Q), which has been reported mostly in S. Typhi and S. Paratyphi A, has been confirmed recently to confer azithromycin resistance in E. coli by cloning ( 34 , 35 ). The first Arg717 substitution was predicted to have emerged around 2010 with travel-related R717Q mutant found in the United Kingdom ( 36 ).…”
Section: Discussionmentioning
confidence: 92%
“…Subsequent to our first description of R717L 51 , a recent study by Zwama and Nishino 60 has provided evidence which indicated steric hindrance and electrostatic effects to be the cause of a change in the relative accessibility of the PBP. This supports the work we report here, and we now significantly expand the scope of that study by providing a quantitative assessment of drug binding and the specific molecular environment within the binding pockets of the pump to further understand the molecular mechanisms of this mutation.…”
Section: Discussionmentioning
confidence: 93%
“…4 ). All of the residues selected for measurements, except D141 and N282, have been shown to contribute to substrate selectivity ( 11 , 56 58 ). Largest average changes during conformational transition were found between DBP residues F178 and F628 (80%), F617 and the PBP residue R717 (43%), and the putative entrance channel residues I38 and I671 (36%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%